Educational leadership in the digital era: overcoming challenges and embracing opportunities of integrating technology in education management - Marshila Kumin,; Michell Fadrick Tong,; Sharima Ruwaida Abbas, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Technology integration in education management holds significant promise for transforming teaching, learning, and administrative processes. However, it also presents challenges that educational leaders must navigate to ensure fair access and maximise learning outcomes for students and educators. This study delves into the complexities educational leaders face as they seek to incorporate technology into education management effectively. This research explores key themes such as collaboration, ethics, access, and resistance to change through a comprehensive review of relevant literature, including databases such as Google Scholar, EBSCO, Scopus, Web of Science, and ScienceDirect. While acknowledging hurdles such as implementation costs and digital disparities, the study also underscores the benefits of technology integration, such as enhanced communication and personalised learning opportunities. By shedding light on these challenges and proposing actionable recommendations, this work contributes to a deeper understanding of how educational leaders can successfully integrate technology into education management practices. Ultimately, this study aims to foster more meaningful technology adoption and improve overall educational outcomes in our increasingly digital world by emphasising the importance of strong leadership, digital literacy, and equal access.